Cooperation and the emergence of maritime clusters in the Atlantic: Analysis and implications of innovation and human capital for blue growth. (July 2015) - Pinto, Hugo; Cruz, Ana Rita; Combe, Colin
Abstract: The so-called 'blue economy' is gaining emphasis in European policy making due to the expansion of its relevance beyond traditional economic sectors but also to new and developing ones that exhibit rapid growth. Much of the discourse has focused on the emergence and consolidation of maritime clusters. However, there has been less attention on the regional development aspect and this article provides a timely contribution to filling the gap in knowledge by presenting the findings and analysis of a survey applied to blue economy organisations in Portugal, Spain, Ireland and Scotland. Specifically, issues of innovation, human capital and social capital provide the basis of inquiry around the creation and consolidation of maritime clusters. The article uses the survey data to understand the determinants of the variety of cooperation dynamics. A key finding reveals that participation in innovation activities and absorptive capacity are critical factors in increasing cooperation. From the analysis it is clear that there are significant discrepancies in participation between sectors, such as tourism where participation rates are below average. The article concludes by defining the core activities that should feature in a maritime cluster. Highlights: The blue economy is having emphasis in European policy making. This article debates the relevance of the maritime clusters for regional development. The results of a survey applied to Atlantic's blue economy are presented. Innovation activities and absorptive capacity are key determinants of cooperation.